CUDA implementation of DES algorithm for lightweight platforms - Güler, Zafer; Özkaynak, Fatih; Çinar, Ahmet (Association for Computing Machinery, 2017)
Our daily life, with the knowledge revolution has entered into a major transformation. For the last few years, with the concept of "internet of things", experts agree that this transformation will affect every part of society and the concept of business. However, this rapid transformation has many problems. One of the most important problems is how to secure the information on digital media? There are many cryptographic solutions to ensure information security. However, since the devices we use in our daily lives have various resource constraints, more efficient algorithms are needed for both memory and processing requirements. In this study, one of the most widely used block encryption algorithms-DES algorithm is implemented on CUDA to investigate what kind of improvements could be made as performance. The analysis and test results show that a more efficient design is obtained than the original DES algorithm. © 2017 Association for Computing Machinery.
2017 International Conference on Biomedical Engineering and Bioinformatics, ICBEB 2017 -- 14 September 2017 through 16 September 2017 -- Bangkok -- 131935
Keywords: CUDA; DES Algorithm; GPU